Comparable estimates of out-of-pocket payment on hospitalisation and outpatient services in India, 2004-18 - Sanjay K. Mohanty; Balakrushna Padhi; Rajeev Ranjan Singh; Umakanta Sahoo (Elsevier, 2022)
Background: Comparable estimates of household health spending and out-of-pocket (OOP) payment on health care in India are a daunting task. Often these estimates are provided for specific services such as maternal care, type of disease, hospitalisation, outpatient care, and an episode of hospitalisation. This paper presents comprehensive and comparable estimates of health spending and out-of-pocket payment on hospitalisation and outpatient care in India over the past 15 years. Methods: A total of 73,868 households in 2004, 65,932 households in 2014, and 113,823 households in 2018 surveyed in the 60th, 71st, and 75th rounds of NSSO health surveys, respectively, were used in the analysis. Descriptive statistics, concentration index, two-part regression, and logistic regression were used in the analysis. Results: The utilisation of hospitalisation services has increased over time. During 2004-18, the mean adjusted OOP payment on hospitalisation at 2018 prices was 308 US$ in 2004,353 US$ in 2014 and 332 US$ by 2018. Reimbursement on medical spending was only 2%, 7% and 11% of medical spending in 2004, 2014 and 2018 respectively. Both medical spending and OOP on inpatient and outpatient care showed large inter-state variations. The OOP payment on inpatient and outpatient care was significantly higher among richer households in urban households, households without health insurance, households having an elderly member and female-headed households. Conclusion: Though the households OOP for outpatient and inpatient, in recent years had declined, OOP as a share of medical expenditure remained high over time and majority of the households are not yet covered under any health protection scheme in India.